Responsiveness of Objective vs. Clinical Balance Domain Outcomes for Exercise Intervention in Parkinson's Disease - Hasegawa, Naoya; Shah, Vrutangkumar V.; Harker, Graham; Carlson-Kuhta, Patricia; Nutt, John G.; Lapidus, Jodi A.; Jung, Se Hee; Barlow, Nancy; King, Laurie A.; Horak, Fay B.; Mancini, Martina (Frontiers in Neurology, 2020)
Background: Balance deficits in people with Parkinson’s disease (PD) are often not helped by pharmacological or surgical treatment. Although balance exercise intervention has been shown to improve clinical measures of balance, the efficacy of exercise on different, objective balance domains is still unknown. Objective: To compare the sensitivity to change in objective and clinical measures of several different domains of balance and gait following an Agility Boot Camp with Cognitive Challenges (ABC-C) intervention. Methods: In this cross-over, randomized design, 86 individuals with PD participated in 6-week (3x/week) ABC-C exercise classes and 6-week education classes, consisting of 3-6 individuals. Blinded examiners tested people in their practical Off state. Objective outcome measures from wearable sensors quantified 4 domains of balance: sway in standing balance, anticipatory postural adjustments (APAs) during step initiation, postural responses to the push-and-release test and a 2-minute natural speed walk with and without a cognitive task. Clinical outcome measures included the Unified Parkinson’s Disease Rating Scale (UPDRS) and its subscales, the Mini Balance Evaluation Systems Test (Mini-BESTest), the Activities of Balance Confidence (ABC) and the Parkinson’s Disease Questionnaire (PDQ-39). The standardized response means (SRM) of the differences between before and after each intervention compared responsiveness of outcomes to intervention. A linear mixed model compared effects of exercise with the active control – education intervention. Results: The most responsive outcome measures to exercise intervention with an SRM > 0.5 were objective measures of gait and APAs, specifically, arm range of motion, gait speed during a dual-task walk, trunk coronal range of motion, foot strike angle, and first step length at step initiation. The most responsive clinical outcome measure was the patient-reported PDQ-39 activities daily living subscore but all clinical measures had SRMs < 0.5. Conclusions: The objective measures were more sensitive to change after exercise intervention compared to the clinical measures. Spatio-temporal parameters of gait, including gait speed with a dual-task, and APAs were the most sensitive objective measures and perceived functional independence was the most sensitive clinical measure to change after the ABC-C exercise intervention. Future exercise-intervention to improve gait and balance in PD should include objective outcome measures.